Authoritarianism, Violence and Elites in Nicaragua. Notes about the Crisis (2018-2019) - Monte, Antonio (2020)
The Nicaraguan crisis demands an interrogation of authoritarianism in its long duration. In this regard, in this article we reflect on two problems: first, genealogies of authority repeatedly lead to the failure of politics and, consequently, to the use of violence; second, the significant contribution of elites to the persistence of authoritarianism, by co-opting the democratic functioning of institutions or by strengthening a culture of pacts evident in contexts of crisis and political transition. A politically sustainable future involves questioning the essence of politics, as we have built it socially and culturally.